If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x=45-(x/3)
We move all terms to the left:
2x-(45-(x/3))=0
We add all the numbers together, and all the variables
2x-(45-(+x/3))=0
We multiply all the terms by the denominator
2x*3))-(45-(+x=0
We add all the numbers together, and all the variables
x+2x*3))-(45-(=0
Wy multiply elements
6x^2+x=0
a = 6; b = 1; c = 0;
Δ = b2-4ac
Δ = 12-4·6·0
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1}=1$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-1}{2*6}=\frac{-2}{12} =-1/6 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+1}{2*6}=\frac{0}{12} =0 $
| 4/4=n/6 | | x+x+x+6=78 | | 4=8q-6q | | y=59+1 | | 6b-10=2(b-11)+4(b-2) | | 16y-24=-18+9y | | 2x^2-4=30 | | -7/8z=-1/5 | | 25x+21=-15(8x-25)-2x | | x/3-45=2x | | h+8=-27 | | x/3=45-2x | | 12.9x=16 | | (x2+5)-6=(9x+18)3 | | 2x-8=x+59 | | 5y+7=-14+8y | | 4(-8+5)=32x=26 | | 8(3x-7)=-6(x+7) | | -2x^2+52x+240=0 | | 5m−m=8 | | -2-8r=-8-2r | | x-7+3=5 | | -3(23x+6)=-26 | | 3(2+8b)-5(-6b+7)=79 | | 6x-2+2x=-2+4x+8 | | 30+15x=165 | | 2/7y-5/61=1/6-5/7y= | | z5− -14= 18 | | 15(x-13)=495 | | −3(23x+6)=−26 | | 5x+2=127x= | | 15(x-13)=12 |